Effectiveness of Lipopolysaccharide (LPS) Induction in Wistar Rats as a Low Birth Weight (LBW) Model - Geneung Patridina; Nugrahanti Prasetyorini (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: Low birth weight (LBW) is linked to stunting, neurodevelopmental delays, and neonatal mortality of up to 80%, with risk factors including maternal infection, poor nutrition, gestational age, obstetric history, and socioeconomic conditions. This study assessed the effectiveness of lipopolysaccharide (LPS) induction in Wistar rats as an LBW model, given LPS’s ability to mimic maternal infection and induce a controlled inflammatory response, while addressing the lack of updated data on inflammatory mediators such as VEGF, TNF-α, and IL-6 in LPS-induced LBW. Material and Methods: Four groups of Wistar rats were used in an in vivo true experimental post-test only design. LPS injection as the independent variable, and the dependent variables include TNF-α and IL-6 levels in the mother's serum and amniotic fluid as determined by ELISA, fetal weight, mortality, crown-rump length, and tail length. Distribution-appropriate statistical tests were used to assess the data, and a p-value of less than 0.05 was considered significant. Results: Administration of LPS (50–100 µg/kg) significantly reduced fetal weight (p=0.04) and increased mortality. The fetal weight decreased by 57.4% in LPS100, and 32 deaths occurred compared to the control group. Crown-rump length (CRL) also significantly decreased at doses of 75 and 100 µg/kg (p<0.05), while tail length showed no significant difference (p>0.01). Additionally, LPS increased IL-6 and TNF-α levels compared to the control (p<0.05), with significant increases in the LPS75 and LPS100 groups compared to LPS50 (p<0.001). Conclusion: LPS induction in Wistar rats decreases birth weight, CRL, and increases fetal mortality, IL-6, and TNF-α, but does not affect fetal tail length.